A North-South agent based model of segmented labour markets: The role of education and trade asymmetries - Lucrezia Fanti; Marcelo C. Pereira; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
Drawing on the labour-augmented K+S agent-based model, this paper develops a two-country North-South ABM wherein the leader and the laggard country interact through the international trade of capital goods. The model aims to address sources of asymmetries and possible converge patterns between two advanced economies that are initially differentiated in terms of the education level they are able to provide. Education is modeled as a national-level policy differently targeting the three usual levels, that is primary, secondary and tertiary. After being educated and entering the labour force, workers face a segmented market, divided into three types of job qualification, and the resulting position levels inside firms, i.e., elementary, technical and professional occupations. The three resulting labour market segments are heterogeneous in terms of both requested education level and offered wages. To address the role of trade and education, we experiment with different education-policy and trade settings. Ultimately, we are interested in understanding the coupling effects of asymmetries in education, which reverberate in segmented labour markets and differentiated growth patterns. Notably, our focus on capital-goods trade, rather than consumption goods, allows us to assess a direct link between productive capabilities in producing complex products and country growth prospects.
Keywords: C63; J3; E24; O1; 330; Agent-Based Model; Education; International Trade; Technology Gap; Labour Market